The Socio-political Relevance of the Indian Smart City Mission: ACritical Analysis - Saha, Apala (National Geographical Journal of India, 2022)
The world is becoming more and more urbanised by the day. India also is all set to become an urban majority nation by the mid-twenty-first century. Most of India's urbanisation seems unplanned and mismanaged leading to a host of social problems like slum extensions, social exclusions, absence of basic accessibilities with the widespread prevalence of social injustice and the process has been majorly attributed to migrants from rural areas. Post-independence plans exhibit several instances of correcting congestions in India's big cities through the creation of alternate absorption points. With this background in mind, the paper goes on to argue that, the urbanisation of mid-sized cities have proven to be mostly unimpressive, failing to relieve the big cities, thereby generating a top-heavy structure. It further finds, through an extensive content analysis that the Smart City Mission was introduced to rid the Indian cities of its long-pending issues by enabling big cities to accommodate better and most importantly empowering mid-sized cities to emerge as centres of growth. However, following the tradition of a certain kind of project-based urbanisation; the mission appears to have inherited vulnerabilities like hierarchical power structures, inadequate local bodies, the dependence of private players, exploitative market forces and inter-group and inter-spatial conflicts from its predecessors like the JNNURM. Undoubtedly, the intent has been to learn from the past but the basic federal structure of governance, the complex socio-spatial dynamics, the varied stakes and concerned stakeholders causes one to re-think if the mission can entirely be a success and create cities which can globally be identified as smart